ENGINEERING TRAINING OF BACHELORS OF TECHNICAL SPECIALTIES IN ACCORDANCE WITH MODULAR APPROACH PRINCIPLES - Arstan M. Gazaliyev; Viktor V. Egorov; Iosif V. Breydo (Высшее образование в России, 2016)
Experience in organization of engineering students training at the Karaganda State Technical University according to the bachelor degree program on the basis of metasubject principles within modular approach is presented. The core element of the programfastening various disciplines of a module in a whole is an actual complex project. The perspective direction for course and diploma engineering projects can be considered creation of educational equipment by students of various courses working in one team. This approach, on the one hand, provides, continuous updating of laboratory base used for knowledge-intensive, dynamically developing specialties, and on the other hand, enables to organize elite bachelor technical training.